Hadith #5102 - Sunan Abi Dawud - Abdullah ibn 'Amr bin Haram; al-Laith bin Sa'd الليث بن سعد; Jabir ibn 'Abdullah; Khalid bin Yazid خالد بن يزيد الجمحي الإسكندراني; Qutayba bin Sa'id bin Jamil قتيبة بن سعيد بن جميل; Sa'id bin Abi Hilal سعيد بن أبي هلال الليثي; Yazid bin 'Abdullah bin Usama B. al-Haad يزيد بن عبد الله بن أسامة بن الهاد (Sunan Abi Dawud)
when you hear the cocks crowing, ask Allah for some of His grace, for they have seen as angel; but when you hear an ass braying, seek refuge in Allah from the devil, for it has seen the devil.
Grade: Sahih